2011
DOI: 10.1039/c1nr10079c
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of affinity of molecules for carbon nanotubes

Abstract: Recent developments of non-covalent functionalization of carbon nanotubes (CNTs) require a systematic understanding of the interaction between molecule and CNTs (CNT-molecular interaction); however, it has been difficult to evaluate the "net" interaction between the CNTs and molecules. We now use silica gel particles coated with the pristine single-walled carbon nanotubes (SWNTs) in a monolayer fashion as the stationary phase of a HPLC column. The newly developed column (SWNT-column) worked as a powerful tool … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(53 citation statements)
references
References 81 publications
1
49
0
Order By: Relevance
“…Table 1 summarizes the results of these experiments for all the aromatic boronic acids and demonstrates that the observed optimal coating concentrations were lowest for pyrene-1 boronic acid (2 mM), followed by 14 mM for 9-phenanthracenyl boronic acid, 41 mM for naphthalene-1 boronic acid and 70 mM for phenyl boronic acid. These values are in good agreement with other observations, including those of Yoo et al [37] that demonstrated that retention of aromatics on immobilized single-walled CNTs solid-phase column, which is a qualitative metric for binding affinities was benzene < naphthalene < phenanthrene < pyrene.…”
Section: Resultssupporting
confidence: 82%
“…Table 1 summarizes the results of these experiments for all the aromatic boronic acids and demonstrates that the observed optimal coating concentrations were lowest for pyrene-1 boronic acid (2 mM), followed by 14 mM for 9-phenanthracenyl boronic acid, 41 mM for naphthalene-1 boronic acid and 70 mM for phenyl boronic acid. These values are in good agreement with other observations, including those of Yoo et al [37] that demonstrated that retention of aromatics on immobilized single-walled CNTs solid-phase column, which is a qualitative metric for binding affinities was benzene < naphthalene < phenanthrene < pyrene.…”
Section: Resultssupporting
confidence: 82%
“…On the other hand, fullerenes as well as CNTs exhibit a mobilization potential for various organic pollutants [62], such as lindane (agricultural insecticide) [63] and persistent polychlorinated biphenyls [64]. The significant advantages of CNMs comprise their enormous surface area, mechanical and thermal stability, high chemical affinity for aromatic compounds [65], and potential antibacterial properties (described below). Moreover, contaminants can be desorbed from CNMs, and therefore, filters based on CNMs can be recycled [66,67].…”
Section: Environmental Applications Of Carbon-based Nanomaterialsmentioning
confidence: 99%
“…Zhang et al reported that the base sequence and chain-length of oligo-DNAs affected SWNT-sorting18 and the kinetics of the ssDNA replacement by a surfactant on the surfaces of the (6,5)SWNTs based on the analysis of Eyring's theory of absolute reaction rates 1920. Molecular adsorption2122232425 and chromatography26272829 using SWNT-coated silica spheres have been reported as useful methods for assigning the order of interactions between some organic molecules and SWNTs. Molecular dynamic simulations also have been reported to understand the interaction of DNA and SWNTs303132333435.…”
mentioning
confidence: 99%